Sonographic evaluation of abdominal organs in a sickle cell disease patient - Kaushal, Lovely; Verma, V K; Ahirwar, C.P.; Patil, A; Pratap Singh, Shakti (International Journal of Medical Research and Review, 2014)
Background: SCD is one of the most common inherited hemoglobinopathies worldwide. It is a major health problem in Madhya Pradesh and surrounding states. The present study was undertaken to infer the value of ultrasonography in evaluating abdominal organs in a SCD patient. Study design: This is a prospective hospital based study. Method: 100 SCD patients were assessed for abdominal pathologies by USG, the results thus analyzed and prevalence was calculated. Result: Hepatomegaly is the most common association observed in 69% of patients followed by splenomegaly in 31% patients & increased renal size in 29% patients. Cholelithiasis (17%), increased renal medullary echogenecity (14%), Auto-splenectomy (11%), Bright liver (9%), Splenic calcification (8%), Increased GB wall thickness (6%), Splenic infarct (5%) and Increased pancreatic echogenicity (3%) are the other associated findings. Conclusion: Real time ultrasonography is a simple, cheap, rapid, easily accessible, non-invasive, non-ionizing screening procedure in all cases of SCD patient for assessment of pathological changes occurring in the various abdominal organs. The high rates of abdominal pathologies being diagnosed on ultrasonography underscores the need for it to be established as a standard screening procedure with established protocols.